2017
DOI: 10.1074/jbc.m116.748707
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of a Stable Effector Functionless (SEFL) Monoclonal Antibody Scaffold in Vitro

Abstract: Edited by Peter CresswellThe stable effector functionLess (SEFL) antibody was designed as an IgG1 antibody with a constant region that lacks the ability to interact with Fc␥ receptors. The engineering and stability and pharmacokinetic assessments of the SEFL scaffold is described in the accompanying article (Jacobsen, F. W., Stevenson, R., Li, C., Salimi-Moosavi, H., Liu, L., Wen, J., Luo, Q., Daris, K., Buck, L., Miller, S., Ho, S-Y., Wang, W., Chen, Q., Walker, K., Wypych, J., Narhi, L., and Gunasekaran, K. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…It has been shown that the Tm of CH2 with mutations in L242C and L334C in IgG1 is 8.7°C higher than that in wtIgG1 ( 79 ). In another research ( 80 ), to improve the stability of an IgG1 variant with mutation of N297G (mAbW.IgG1, an effector function silenced IgG1), an additional disulfide bond according to the design of m01 was introduced between position L242 and K334 ( 81 ). As expected, the stability of this IgG1 variant (mAbW.SEFL2.0) with mutations on L242C/N297G/K334C is improved particular in the thermal stability, but it shows faster clearance in the rat in pharmacokinetics study.…”
Section: Increase Of Physicochemical Properties Of Fc Fragmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the Tm of CH2 with mutations in L242C and L334C in IgG1 is 8.7°C higher than that in wtIgG1 ( 79 ). In another research ( 80 ), to improve the stability of an IgG1 variant with mutation of N297G (mAbW.IgG1, an effector function silenced IgG1), an additional disulfide bond according to the design of m01 was introduced between position L242 and K334 ( 81 ). As expected, the stability of this IgG1 variant (mAbW.SEFL2.0) with mutations on L242C/N297G/K334C is improved particular in the thermal stability, but it shows faster clearance in the rat in pharmacokinetics study.…”
Section: Increase Of Physicochemical Properties Of Fc Fragmentmentioning
confidence: 99%
“…A major concern is that deglycosylation will lead to instability and aggregation. Hence, the IgG1 scaffold with stable effector functions missing ( 81 ) needs to be further optimized. Based on the computational modeling, two variants mAbW.SEFL2.1 and mAbW.SEFL2.2 with tri-mutations on A287C/N297G/L306C and R292C/N297G/V302C, respectively, as mentioned earlier showed improved stability, decreased clearance rate, and longer half-life ( 80 ), which could be used for development of therapeutic mAbs without effector functions.…”
Section: Relationships Between Physicochemical Properties and Clinicamentioning
confidence: 99%
“…Although SEFL2.2 is an efficient strategy to reduce Fc binding to FcγRI, FcγRIIA and to FcgRIIIA receptors ( Jacobsen et al., 2017 ; Liu et al., 2017 ), little is known about its mechanism of action. To unveil the molecular basis that mediates the loss of Fcγ receptor activity for SEFL2.2, we compared this structure with the co-crystal structures of 3 Fcγ receptors [FcγRI (PDB: 4X4M ), FcγRIIA (PDB: 3RY6 ) and FcγRIIIA (PDB: 5XJE )], each determined in complex with WT Fc ( Figure 2 A) ( Lu et al., 2015 ; Ramsland et al., 2011 ; Sakae et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The charge pair mutations create a heteroimmunoglobulin molecule with two distinct antigen-binding fragments (Fabs). By virtue of the absence of an Fc glycan, AMG 966 is a stable effector functionless (SEFL) antibody, which lacks the ability to interact with Fcγ receptors ( 11 ).…”
Section: Introductionmentioning
confidence: 99%